Evaluasi Penggunaan Model Kahoot dalam proses Pembelajaran Berbasis Digital di Madrasah Tsanawiyah Negeri Kota Bengkulu - Zazali Juwita; Salsabila Salsabila; Bayu Nugraha; Nurniswah Nurniswah (UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: The digital-based learning process still creates difficulties for students to see that students are not interested and bored in learning, so it requires an active, effective and fun kahoot learning model. The purpose of this study is to evaluate the use of the kahoot model in the digital-based learning process at Madrasah Tsanawiyah Negeri Bengkulu City. Using a descriptive qualitative method of the CIPP approach (context, input, process and product). The results of the study show that digital-based learning programs are generally good, but the kahoot model program in the digital learning process cannot be applied by all teachers and students, because there are still teachers and students who have limited equipment and optimal technological literacy. The input of the kahoot model in the digital-based learning process in general is good, but there are still some student teachers and teachers who are not ready with digital learning, financing, infrastructure facilities and curriculum. The process of using the kahoot model in the digital-based learning process in general is good such as fun and game-based learning, encouraging active participation, accelerating material understanding, and motivating students to focus more on learning, and keeping the learning atmosphere interesting and dynamic. However, there are still teachers who seem less interesting and boring in learning because they are not able to implement digital-based learning. Meanwhile, the product of using the kahoot model in the digital-based learning process in general is good, seeing the many achievements obtained by students, both academic and non-academic achievements, and 100% of student graduates can continue their education to a higher level. So it can be concluded that the results of the evaluation of the use of the kahoot model can improve the digitalbased learning process in madrasas. Thus, it can be suggested that to improve the digital-based learning process, increase the use of the kahoot learning model in madrasah.Keywords: Evaluation, Use of Kahoot Model, Digital-Based Learning Process, Madrasah Tsanawiyah Negeri Bengkulu City. Abstrak: Proses pembelajaran berbasis digital masih menciptakan kesulitan bagi siswa terlihat siswa tidak tertarik dan bosan dalam pembelajaran, sehingga membutuhkan model pembelajaran kahoot yang bersifat aktif, efektif dan menyenangkan. Tujuan penelitian ini untuk mengevaluasi penggunaan model kahoot dalam proses pembelajaran berbasis digital di Madrasah Tsanawiyah Negeri Kota Bengkulu. Menggunakan metode kualitatif deskriptif pendekatan CIPP (conteks, input, proses dan produk). Hasil penelitian menunjukkan bahwa program pembelajaran berbasis digital secara umum sudah bagus, namun program model kahoot dalam proses pembelajaran digital tidak semua guru dan siswa dapat diterapkan, karena masih terdapat guru dan siswa memiliki keterbatasan peralatan dan literasi teknologi secara optimal. Input model kahoot dalam proses pembelajaran berbasis digital secara umu sudah bagus, namun masih terdapat beberapa guru siswa dan guru tidak siap dengan pembelajaran digital, pembiayaan, sarana prasarana dan kurikulum. Proses penggunaan model kahoot dalam proses pembelajaran berbasis digital secara umum sudah bagus seperti pembelajaran menyenangkan dan berbasis permainan, mendorong partisipasi aktif, mempercepat pemahaman materi, serta memotivasi siswa untuk lebih focus belajar, dan menjaga suasana pembelajaran tetap menarik dan dinamis. Namun masih terdapat guru terkesan kurang menarik dan membosankan dalam pembelajaran karena tidak mampu menerapkan pembelajaran berbasis digital. Sedangkan produk penggunaan model kahoot dalam proses pembelajaran berbasis digital secara umum sudah bagus terlihat banyaknya prestasi yang didapatkan oleh siswa baik prestasi akademik maupun non akademik, dan lulusan siswa 100 % dapat melanjutkan pendidikan ke jenjang satu tingkat lebih tinggi. Sehingga dapat disimpulkan bahwa hasil evaluasi penggunaan model kahoot dapat meningkatkan proses pembelajaran berbasis digital di madrasah. Dengan demikian dapat disarankan bahwa untuk meningkatkan proses pembelajaran berbasis digital, maka tingkatkan penggunaan model pembelajaran kahoot di madrasah.Kata kunci: Evaluasi, Penggunaan Model Kahoot, Proses Pembelajaran Berbasis Digital, Madrasah Tsanawiyah Negeri Kota Bengkulu.